Ceramic trade between Quanzhou and the Malay Peninsula from the eleventh to the thirteenth centuries: based on Chinese texts and shipwreck archaeological data - Feiran, Wang; Asyaari Muhamad; Yasmin Amirah Muhammad Edrus (Penerbit UKM, 2025)
Quanzhou, located in Fujian Province on the southeastern coast of China, rose to prominence as an international trading port in the eleventh century, and overseas trade with the Malay Peninsula took on new dimensions. This article takes the development of ceramic trade as an example, combining ancient literature and archaeological reports of shipwrecks containing Minnan (Southern Fujian) porcelain, to analyze the dynamic interaction and the maritime trade between the Quanzhou region with the Malay Peninsula from the eleventh to the thirteenth centuries. This study uses documentary research, archaeological typology, and comparative research. The findings indicate that the open maritime trade policy not only consolidated the vital position of the Quanzhou port on the South China Sea route but also spawned kilns near the port, with the primary purpose of exporting, which significantly increased the proportion of ceramics from the Minjiang River Basin in the overall ceramic trade.